Evaluation of land preparation methods for soil stabilization, revegetation, and renewed productivity in semi‐arid climates - Jarrett Lardy; Tom DeSutter; Miranda Meehan; Aaron Daigh; James Staricka; Nathan Derby (Agrosystems, Geosciences & Environment, 2023)
Abstract In the Williston Basin, land‐preparation treatments have not been compared in side‐by‐side trials to evaluate performance for parameters such as runoff, erosion, and vegetation establishment. Thus, four treatments of wheat‐straw crimping, land imprinting, wood‐fiber hydromulch, and the combination of land imprinting and hydromulch were evaluated against a bare soil control in a replicated and randomized completed block field experiment near Williston, ND. Rainfall simulations were performed in September 2020 and June 2021 to examine the effectiveness of the treatments to reduce runoff and sediment losses. Vegetation establishment was also evaluated in August 2021. The wheat straw treatment reduced the equivalent depth of runoff by 60% as compared to the bare soil control in 2021. By 2021, the imprinted area had largely become similar in roughness as the control plots and thus sediment losses were not different between these treatments. However, relic effects of the straw and hydromulch treatments reduced sediment loss by 50% or more. Vegetation establishment was not significantly different among treatments and the bare soil control using broadcast seeding, which may have been due to drought conditions causing low establishment in all plots. All the land‐preparation practices evaluated in this study may have limitations in assisting plant establishment during severe or persistent droughts.